The Effect of Implementing Online Presence With Selfi Application and Work Discipline on Employee Performance - Putri, Rizki Dila; Fuadi, Fatih; Selvina, Mia (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to determine the effect of online attendance and work discipline on employee performance at the Regional Revenue Agency (BAPENDA) of Lampung Province of Lampung Province. The method used is a questionnaire with 30 respondents selected from the employees of the Regional Revenue Agency (BAPENDA) of Lampung Province of Lampung Province. This study is quantitative in nature. The data analysis technique employed in this research is PLS (Partial Least Square) using the SmartPLS 3.0 software. The findings of the study indicate that online attendance has a positive and significant effect on employee performance, and work discipline also shows a positive and significant result on employee performance. From an Islamic perspective, performance is not only measured by productivity but also by spiritual values such as trustworthiness, integrity, and responsibility. This research is conducted with an Islamic perspective and focuses on the employees of the Regional Revenue Agency (BAPENDA) of Lampung Province (BAPENDA) of Lampung Province.